IPM Technology and Its Incentives to Rice Farmers in Yogyakarta Province - Irham Irham (Universitas Gadjah Mada, 2002)
Negative externality impacts on environment and human health are the consequences of continuous and heavy use of chemical pesticides. It has also brought about adverse effects towards agricultural production since it was found that only 1 % of the inputs was absorbed by the plants, while the rest was left to the environment as poisonous waste. Realizing such serious problems the Indonesian government waived subsidy for chemical pesticides in 1989 and at the same time Integrated Pest Management (IPM) program was introduced. To see the superiority of IPM technology it is important to evaluate the program in two ways: (l) evaluating whether the IPM technology has successfully reduced the use of chemical pesticides, and (2) what incentives the IPM technology provides to the farmers in coping with the risk of crop loss due to the pest damage. The study found the IPM technology successfully reduced the application of chemical pesticides in Yogyakarta province without sacrificing the level of rice output for the farmers. The study concludes that IPM technology provides incentives to the farmers in the form of lower pest damage, lower crop loss, and better yield so that the farmers are willing to adopt this technology in their rice farming.